Observation of coherent x-ray production by 800-MeV electrons in a periodic triple-crystal target - Andreyashkin M. Yu.; Zabaev V. N. Viktor Nikolaevich; Kaplin V. V. Valery Viktorovich; Uglov S. R. Sergey Romanovich; Nakayama K.; Endo I. (1997, 1997)
Title screen